2020
DOI: 10.1021/acssuschemeng.0c08230
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Multiple Enzymelike Activity of PtPdCu Trimetallic Nanostructures for Detection of Fe2+ and Evaluation of Antioxidant Capability

Abstract: Metallic nanozymes attracted broad interest because of their efficient catalytic activities and wide applications in biological detection and therapeutics. In this study, PtPdCu trimetallic nanoalloys (TNAs) are prepared by chemical coreduction of Pt2+, Pd2+, and Cu2+ in an aqueous solution. The formation of PtPdCu TNAs is characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy-dispersive system (EDS), and X-ray photoelectron spectroscopy (XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 44 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…17 In addition, the Pd(0) binding energies of Pd 3d 5/2 and Pd 3d 3/2 in PDA-PdCu are slightly positively shifted compared to those in PDA-Pd, suggesting an electron pass route from Pd to Cu. 19,43 These results demonstrate that the electronic states of Pd are successfully modulated by PDA coating and Cu doping. Previous literature reported that metallic state is more beneficial to boost the catalytic activity of precious metals.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…17 In addition, the Pd(0) binding energies of Pd 3d 5/2 and Pd 3d 3/2 in PDA-PdCu are slightly positively shifted compared to those in PDA-Pd, suggesting an electron pass route from Pd to Cu. 19,43 These results demonstrate that the electronic states of Pd are successfully modulated by PDA coating and Cu doping. Previous literature reported that metallic state is more beneficial to boost the catalytic activity of precious metals.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
“…22,23 The surface structures and properties of nanozymes, including morphology, rigidity, wettability, charge, etc., can be modified with metal ions, small molecules, and polymers. 19,22 Till now, various types of polymers, such as polylactic acid, 24 polyethyleneimine, 25 and polydopamine (PDA), 26 have been verified as a coating on the surface of nanomaterials. In comparison, PDA coating polymerized from dopamine is superior to other polymers because PDA can virtually deposit onto and form functional coatings on the surfaces of nearly all types of organic and inorganic materials due to its intrinsic adhesive and cohesive properties as well as abundant functional moieties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pt based and metal oxide) oen function to mimic multiple redox enzymes (oxidase, SOD, peroxidase and catalase). [21][22][23][24][25] Such multiple enzymelike activity enables nanozymes with antioxidant activity while also having pro-oxidative functions. Therefore, it is highly required to develop ideal antioxidant nanomaterial with high efficiency and broad spectrum for biomedical study and clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Different types of noble metal NPs, such as Au, Ag, platinum group metals (Pd, Pt, Ru, Rh, Os, Ir), and their alloy NPs, have been widely used in different fields, including sensing, biomedicine, and catalysis. [ 104–112 ]…”
Section: Engineering Biocatalytic and Antioxidant Nanostructures: Rational Design And Catalytic Activitiesmentioning
confidence: 99%